1988
DOI: 10.1080/00288330.1988.9516295
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary survey for crassulacean acid metabolism (CAM) in submerged aquatic macrophytes in New Zealand

Abstract: This preliminary survey covered 13 aquatic macrophytes present at two sites in Lake Taupo and two sites in the Auckland region (northern half of the North Island, New Zealand). Three species previously unrecorded as CAM plants, Isoetes kirkii A. Braun, Lilaeopsis lacustris Hill, and Vallisneria spiralis Graeb., exhibited diurnal fluctuations in titratable acidity and malic acid content. The changes in titratable acidity varied seasonally from 97 (Dec. 1985) to 46 (June 1986) microequivalents per gram fresh wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
2
13
1
Order By: Relevance
“…The report here of CAM in O. alismoides at low CO 2 contrasts with the data from (Webb et al 1988) where a diel change of only 7 μequiv g -1 FW…”
Section: Distribution Of Biochemical Ccms In Terrestrial and Aquatic contrasting
confidence: 99%
See 2 more Smart Citations
“…The report here of CAM in O. alismoides at low CO 2 contrasts with the data from (Webb et al 1988) where a diel change of only 7 μequiv g -1 FW…”
Section: Distribution Of Biochemical Ccms In Terrestrial and Aquatic contrasting
confidence: 99%
“…Diel changes in acid contents in other Hydrocharitaceae such as species from the genera Egeria, Elodea and Lagarosiphon are relatively low (Keeley 1998;Webb et al 1988). Earlier studies reported fixation of 14 C into C 4 acids in species of freshwater Hydrocharitaceae within the genera: Egeria, Elodea and Lagarosiphon (Brown et al 1974;Browse et al 1977;Degroote and Kennedy 1977;Salvucci and Bowes 1983) and also in the marine Halophila (Beer 1989) although there is little evidence for turnover in pulse-chase experiments.…”
Section: Distribution Of Biochemical Ccms In Terrestrial and Aquatic mentioning
confidence: 99%
See 1 more Smart Citation
“…It has a rosette of quill-like leaves arising from a conn/ root system and exhibits diurnal acid fluctuations only in the green parts of the "quills" (Webb et al 1988). At the study site, Three Mile Bay, Lake Taupo (38°45'S, 175°50'E), it exists in a well-established, shallow-water (1.0-2.5 m) low mixed community (Brown 1975), often in nearly monospecific stands.…”
Section: Methodsmentioning
confidence: 99%
“…Crassulacean acid metabolism (CAM), with its marked diel fluctuations in malic acid content, has been reported in several submerged aquatic plant species (Keeley 1981(Keeley ,1982Keeley & Morton 1982;Boston & Adams 1983;Richardson et al 1984;Webb et al 1988;Morton & Keeley 1990;Gacia & Penuelas 1991;Keeley & Sandquist 1991). The magnitudes of the diel fluctuations are influenced by several environmental factors (e.g., photosynthetically active radiation (PAR), temperature, CO2).…”
Section: Introductionmentioning
confidence: 99%